2022
DOI: 10.3390/foods11213311
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Performance of Plant Protein Concentrates as Partial Meat Substitutes in Hybrid Meat Emulsions

Abstract: Hybrid meat products are an excellent strategy to incorporate plant proteins into traditional meat formulations considering recent market trends focusing on the partial reduction in red meat content. In this work, we evaluated the effects of different concentrated plant proteins (soy, pea, fava bean, rice, and sunflower) in partially replacing meat in meat emulsion model systems. Soy, pea, and sunflower proteins showed great compatibility with the meat matrix, giving excellent emulsion stability and a cohesive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
0
1
0
1
Order By: Relevance
“…The burger formulations made with chitosan (PPI-CH and SPI-CH) registered the highest hardness, shear force and cohesiveness, but also the highest gumminess, while those made with xanthan as a cold-gelling agent, with both pea and soy proteins, registered the lowest hardness, shear force and chewiness, significantly (p < 0.05) lower than those of the control burgers. These results could be related to the higher hardness of the emulsion gels made with chitosan (as previously presented in Table 2), but also to the higher water loss found in the burgers reformulated with emulsion gels based on chitosan, as it is well-known that water influences texture by acting as a plasticizer, with meat products with higher water loss presenting a higher hardness [25]. Based on the same principle, the lowest hardness values found in the burgers reformulated with emulsion gels based on xanthan (PPI-X and SPI-X) could be attributed to their highest moisture retention.…”
Section: Texture Analysis Of Burgersmentioning
confidence: 57%
See 2 more Smart Citations
“…The burger formulations made with chitosan (PPI-CH and SPI-CH) registered the highest hardness, shear force and cohesiveness, but also the highest gumminess, while those made with xanthan as a cold-gelling agent, with both pea and soy proteins, registered the lowest hardness, shear force and chewiness, significantly (p < 0.05) lower than those of the control burgers. These results could be related to the higher hardness of the emulsion gels made with chitosan (as previously presented in Table 2), but also to the higher water loss found in the burgers reformulated with emulsion gels based on chitosan, as it is well-known that water influences texture by acting as a plasticizer, with meat products with higher water loss presenting a higher hardness [25]. Based on the same principle, the lowest hardness values found in the burgers reformulated with emulsion gels based on xanthan (PPI-X and SPI-X) could be attributed to their highest moisture retention.…”
Section: Texture Analysis Of Burgersmentioning
confidence: 57%
“…Previous studies reported that formulations with higher pH values were those with better emulsion stability and attributed this behavior to the higher deviation from the isoelectric point of the meat and plant proteins, which affects the net charge of the protein. This contributes to a stronger and more cohesive protein interface on the fat particles and increases the protein interaction with water [25]. No significant (p < 0.05) pH variation was recorded in emulsion gels during 7 days of refrigerated storage.…”
Section: Color Ph and Stability Of Emulsion Gelsmentioning
confidence: 94%
See 1 more Smart Citation
“…Bununla birlikte, modifiye edici katkılar ve polisakkarit karışımları takviyeleri ile artan jelleşme özellikleri, iyi derecedeki emülsifiye ve köpürme özellikleri ile şarküteri benzeri et analoglarının üretimi için uygun protein kaynakları olarak gösterilmektedir [48][49][50][51]. Farklı konsantre bitki proteinlerinin (soya, bezelye, bakla, pirinç ve ayçiçeği) et emülsiyonu model sistemlerinde et yerine etkilerinin değerlendirildiği bir çalışmada, pirinç ve bakla proteinlerinin aksine soya, bezelye ve ayçiçeği proteinlerinin, yüksek emülsiyon stabilitesi ve iyi yağ dağılımına sahip kohezif bir protein ağı sağladığı bildirilmektedir [52] .…”
Section: Tohumlarunclassified
“…In addition to its nutritional value, plant‐based protein is also considered as functional ingredient and playing a variety of roles in food formulations, including thickener and gelling agents, stabilisers for emulsion and foam, and adhesives for lipid and water. It has been reported that the emulsion stability of beef sausages was improved after the addition of lupin protein (dos Santos et al ., 2022). Moreover, faba bean protein powders have been used to make emulsion gels including yogurt and tofu analogues, while mung bean protein, due to its good hydrophobicity and antioxidant resistance, can form an adhesive film that acts as an excellent oxygen barrier (Hadidi et al ., 2022; Zheng et al ., 2022b).…”
Section: Introductionmentioning
confidence: 99%